Pre-conditioning of Equine Bone Marrow-Derived Mesenchymal Stromal Cells Increases Their Immunomodulatory Capacity - Caffi, Valeria; Espinosa, Gabriel; Gajardo, Gonzalo; Morales, Natalia; Durán, María Carolina; Uberti, Benjamín; Morán, Gabriel; Plaza, Anita; Henríquez, Claudio (Frontiers in Veterinary Science, 2020)
Mesenchymal stem/stromal cells (MSCs) are increasingly explored for the treatment of degenerative and inflammatory diseases in human and veterinary medicine. One of the key characteristics of MSCs is that they modulate inflammation mainly through the secretion of soluble mediators. However, despite widespread clinical use, knowledge regarding the effector mechanisms of equine MSCs, and consequently their effectiveness in the treatment of diseases, is still unknown. The objectives of this study were to determine the mechanisms underlying inhibition of lymphocyte proliferation by equine bone marrow-derived MSCs, and to evaluate the effect of pre-conditioning of equine MSCs with different pro-inflammatory cytokines on inhibition of lymphocyte proliferation. We determined that inhibition of lymphocyte proliferation by equine MSCs depends on activity of prostaglandin-endoperoxide synthase 2 and indoleamine 2,3-dioxygenase. Additionally, pre-conditioning of MSCs with TNF-α, IFN-γ or their combination significantly increased the expression of prostaglandin-endoperoxide synthase 2, indoleamine 2,3-dioxygenase, iNOS and IL-6. This upregulation correlated with an increased inhibitory effect of MSCs on lymphocyte proliferation. In conclusion, pre-conditioning of bone marrow-derived MSC increases their inhibitory effect on lymphocyte proliferation in horses.